Strength of fiber concrete (concrete) under local compression according to the theory of plasticity and experimental studies - Kuznietsova, Iryna; Dovzhenko, Oksana; Pohribnyi, Volodymyr; Pants, Volodymyr (Academic journal Industrial Machine Building Civil Engineering, 2022)
Local compression of concrete is often implemented in supporting joints of reinforced concrete structures. As a strength calculation method for this case, a variational method in the theory of plasticity is proposed, which is based on the consideration of the failure stage and takes into account the full set of determining factors of strength: the dimensions of the sample, the shape and dimensions of the loading platform, its location, the ratio of the dimensions of the loading device and the element, type and class of concrete (by taking into account both strength characteristics). In experimental studies, the kinematic schemes of failure adopted in the calculation and the influence of determining factors were confirmed. A comparative analysis of the strength calculated by the proposed method with the experimental one for 78 samples showed that they are sufficiently close.
Keywords: local compression; strength; variational method; theory of plasticity; fiber concrete